13C-CO2 pulse labelling evaluation of water deficit on leaf carbon dynamics and whole plant allocation in fruiting coffee - Nakamya, Janice; Van Laere, Jonas; Merckx, Roel; Hood-Nowtny, Rebecca; Dercon, Gerd (Frontiers in Plant Science, 2025)
Plants experience physiological and metabolic changes in response to water deficit during critical stages, such as fruiting. In coffee, the allocation of fresh assimilates and interplay between leaf orientation, leaf age, and carbon changes are unknown. Understanding these strategies would reveal how coffee plants enhance their survival and productivity under water scarcity. Four-year-old Venecia Arabica coffee clones under water stress were pulse labelled with 13C-CO2 in a greenhouse. Three hours after labelling, leaf punches from young and old leaf pairs were collected at 10, 11, 12, and 13 days of water deficit (50% pot capacity/PC). These were analysed to assess 13C enrichment in relation to carbon assimilation and leaf carbon changes over time. Water deficit significantly decreased carbon assimilation by 20-52% compared to well-watered plants, especially in young leaves (p< 0.05). In addition, old leaves on the sun-exposed side performed better in terms of carbon assimilation than those on the shaded side; however, the orientation effect was not evident under stress. At harvest, approximately 15 days of water deficit, carbon allocation exhibited a marked decline, particularly in young leaves. The plants prioritised the allocation of newly assimilated carbon to roots and shoots, and to a lesser extent, to the fruits to support survival, storage, and production. Notably, carbon redistribution resulted in elevated levels of starch and sugar in fruits (by 33% and 51%, respectively), shoots, and roots, accompanied by a reduction in foliar sugar and cellulose contents in young leaves. These findings highlight the complex survival strategies employed by coffee plants, demonstrating their capacity to optimise resource allocation to storage organs and the potential of old leaves in response to drought. The results offer valuable guidance for coffee breeding programs aimed at enhancing the resilience of Coffea arabica to climate-induced water scarcity.